O Método ACRS (Amplification-Created Restriction Site) na Detecção do Polimorfismo rs2227306 no Gene Interleucina (Il8) e Comparação Interétnica da Distribuição Genotípica - Viana, Aline Cavalcanti (2009)
The single nucleotide polymorphism (SNP) +781(C/T) (rs2227306) in the interleukin 8 gene (IL8) has been largely investigated in case-control association studies. Different methods have been used to genotype individuals for this SNP, but they demand extensive optimization of polymerase chain reaction (PCR) conditions or high cost reagents and equipment. The aim of this study was to develop a simple and efficient assay for the detection of the polymorphism rs2227306 in the IL8 gene and to execute an interethnic comparison of the genotype distribution in different populations. The Amplification-Created Restriction Site (ACRS) method was used for genotyping 174 healthy Brazilian individuals (Whites n=148; Blacks n=26). This method was efficient, reproducible and accurate, since the genotypes were confirmed by sequencing. White Brazilian subgroup showed a genotype distribution similar to HapMap CEU Europeans (p=0.49), but different from a German population, PGA African American and HapMap Sub-Saharan Africans (p